POSSIBILITY REALIZATION OF SUB-DISTRICT PARK AND TPU BASED ON RDTR IN BEKASI CITY - Elisa Ayu Setyawati; Anita Sitawati Wartaman; Benny Benyamin Suharto (Journal of Synergy Landscape, 2022)
To be a sustainable city, the New Urban Agenda (NUA) mandates that every resident must be served by GOS. The GOS provided must be close to the population and evenly distributed in each neighborhood. The neighborhood unit has around 120,000 inhabitants, namely the sub-district. Bekasi City plans in the RDTR to provide sub-district GOS such as a sub-district park and a public cemetery (TPU). The availability of public GOS in Bekasi City is currently 3.73% of the city area in 2019, which is still far from the standard requirement of about 20%. To overcome several problems related to public GOS, especially parks and TPUs, the Bekasi City Government created a program of 1,000 parks spread over 12 sub-districts and preparing TPU land every year. This study aims to examine the possibility of realizing the plan from the government based on the RDTR, land use, and land prices. This research is descriptive with a quantitative approach. Analytical methods used spatial analysis using Geographic Information Systems (GIS) and quantitative descriptive analysis. As a result, the sub-district parks realized about 61% and 39% unrealized, and TPUs about 57% realized and 43% unrealized. The possibility of realization, namely the government's ability, is likely big or small. The possibility of realization can be a direction for development like sub-district priorities based on distribution and quantity. To fulfill the distribution required high costs due to the high price of land. However, to fulfill the quantity, looking for sub-districts with large areas and big opportunities for realization.